Spanish cohort profile, antithrombotic therapy and clinical outcomes at 1 year in the EORP atrial fibrillation long-term registry. (25th November 2020) - Marin, F; Rivera-Caravaca, J; Roldan-Rabadan, I; Perez Cabeza, A; Garcia Seara, J; Bertomeu-Gonzalez, V; Leal, M; Garcia-Fernandez, A; Tercedor Sanchez, L; Ayarra, M; Ciudad, M; Castano, S; et al.
Abstract: Background: Atrial fibrillation (AF) is associated with a high risk of stroke and mortality. Some years ago, the EURObservational Research Programme launched the General Long-Term Registry with the aim to evaluate contemporary management of AF patients in Europe, the current use of vitamin K antagonists (VKAs), direct-acting oral anticoagulants (DOACs) and other AF treatments, in relation to guideline recommendations. Purpose: The present report aims to describe the characteristics of a large database on the management of AF in Spain, using the Spanish cohort included in the EORP-AF Long-Term Registry. Methods: The EORP-AF Long-Term General Registry is a prospective, observational, large-scale multicentre registry sponsored and conducted by the ESC, enrolling AF patients in current cardiology practices in 250 centres from 27 participating ESC countries. Patients were enrolled consecutively when presenting with AF as primary or secondary diagnosis to inpatients and outpatient cardiology services from October 2013 to September 2016. The first Spanish patient in the EORP-AF Long-Term Registry was included in 2014. Initially, the aim was to carry out a follow-up up to 3 years but this was reduced to 2 years by the Executive Committee. To date, only data from the first year of follow-up is available for the Spanish cohort. Results: A cohort of 729 AF Spanish patients was included (57.1% male, median age 75 [IQR 67–81] years, median CHA2DS2-VASc and HAS-BLED of 3 [IQR 2–5] and 2 [IQR 1–2], respectively). A relatively low proportion of patients (634, 87%) received oral anticoagulants (OACs), of which 389 (53.4%) were on VKAs and 245 (33.6%) were on DOACs (rate ratio = 1.59 [95% CI 1.35–1.87], p<0.001). Importantly, there were 98 (13.4%) patients taking concomitantly antiplatelet therapy and OACs; as well as 5.5% of patients were taking parenteral anticoagulation or antiplatelets alone. After 1 year, the proportion of patients on OACs increased from 87.0% to 88.1%. The proportion of DOACs users increased from 33.6% at baseline to 39.9%, partly due to switches from VKA to DOACs in relation to poor time in therapeutic range. At the same time, 34 (4.7%) patients withdrew OACs. During the first year of follow-up, 48 patients (6.6%) died, 7 (1.0%) suffered ischemic strokes and 6 (0.8%) transient ischemic attacks. Of note, there was a substantial rate of major bleeds (ISTH criteria) (57, 7.8%), of which 10 (1.4%) were intracranial haemorrhages. Conclusions: Baseline data of the Spanish cohort are similar to that reported for the whole EORP cohort, including similar stroke and bleeding risks. OAC use slightly increased at 1-year, with low discontinuation rates which could be related with a low incidence of thromboembolic events. However, despite the ∼8% rate of major bleeding in overall, the use of a safer therapy such as DOACs is still low compared to VKAs, being the antiplatelets commonly used concomitantly with OACs Funding Acknowledgement: Type of funding source: Private grant(s) and/or Sponsorship. Main funding source(s): Unconditional grant by Boehringer-Ingelheim